Asymptotics of locally constrained control in optimal parabolic problems - Kapustyan, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct and justify asymptotic solutions of optimal parabolic problems with locally constrained control which depends only on time.